THE CORPORATE GOVERNANCE CHARACTERISTICS AND RISK-TAKING IN THE ISLAMIC FINANCIAL INSTITUTIONS: A THEORETICAL REVIEW - Islam, Md. Mohidul; Bhuiyan, Abul Bashar; Kassim, Aza Azlina Md; Rasli, Salina (International Journal of Shari’ah and Corporate Governance Research, 2021)
The present study intends to examine existing literature and summarized the effects of the corporate governance characteristics on risk-taking and justified with existing most relevant theories in the Islamic financing system. The study extracted available literature from Google Scholar, ProQuest, and Scopus as well as other online data-based. The theoretical review findings summarized that there are two theories such as agency theory and stakeholder theory are considered most relevant for underpinning to justify the literature summary of this study. Moreover, the agency theory explains the role of corporate governance characteristics on the risk-taking of IFIs. The present study also shows the stakeholder theory paradigm that, influences the creates effective measurement of risk-taking and the stakeholders which leads to insolvency, economic collapse, liquidity shortage, financial institution corruption, financial institution scandal, enterprise fall, and monetary instability even misunderstanding amongst the stakeholders that lead to credit risk, liquidity. The study recommendations will be used to develop a research framework to examine relationships between corporate governance characteristics and risk-taking based on empirical data and the findings could be a valuable source of knowledge for policymakers and regulators in the Islamic financial services sectors in the world.